An unexpected co‐crystal structure of the calpain PEF(S) domain with Hfq reveals a potential chaperone function of Hfq. Issue 2 (10th February 2020) - Cresser-Brown, Joel; Rizkallah, Pierre; Jin, Yi; Roth, Christian; Miller, David J.; Allemann, Rudolf K.
Abstract : A co‐crystal structure of the calpain PEF(S) domain bound to the Escherichia coli chaperone Hfq provides insight into the pitfalls of expression of the full‐length heterodimeric calpain I complex. Abstract : Calpain is a Ca 2+ ‐activated, heterodimeric cysteine protease consisting of a large catalytic subunit and a small regulatory subunit. Dysregulation of this enzyme is involved in a range of pathological conditions such as cancer, Alzheimer's disease and rheumatoid arthritis, and thus calpain I is a drug target with potential therapeutic applications. Difficulty in the production of this enzyme has hindered structural and functional investigations in the past, although heterodimeric calpain I can be generated by Escherichia coli expression in low yield. Here, an unexpected structure discovered during crystallization trials of heterodimeric calpain I (CAPN1C115S + CAPNS1ΔGR) is reported. A novel co‐crystal structure of the PEF(S) domain from the dissociated regulatory small subunit of calpain I and the RNA‐binding chaperone Hfq, which was likely to be overproduced as a stress response to the recombinant expression conditions, was obtained, providing unexpected insight in the chaperone function of Hfq.